THOUGHT STOPPING TECHNIQUE GROUP COUNSELING TO REDUCE ACADEMIC ANXIETY - Anjani, Liza; Sinaga, M. Harwansyah Putra (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2024)
The large number of students who experience academic anxiety and the challenges they face in completing their final assignments are the impetus for conducting this research. Students who feel academic anxiety or also called academic anxiety due to lack of confidence in their abilities in carrying out academic activities, are generally motivated by several factors such as the desire to graduate on time, high parental expectations, and pressure from supervisors. The aim of this research is to reduce academic anxiety in final year students by using thought stopping strategies in group counseling. Purposive sampling is used in the pre-experimental design quantitative research methodology which has a one-group pre-test-post-test design pattern. Seven students with high levels of academic anxiety will be research participants. They will receive treatment in the form of group counseling using thought stopping techniques. Four sessions were held to conduct this research. T-Test statistical samples with SPSS For Windows Version 26.0 statistical software were used in the data analysis procedure. The findings of this study show the effectiveness of thought stopping strategies in group counseling to reduce academic anxiety. The acceptance of the alternative hypothesis (Ha) is indicated by the results of the Paired Sample T-Test analysis which produces a significant probability value (2-tailed) < 0.05. It was found that after the final students underwent group counseling treatment using the thought stopping technique, there was a significant reduction in anxiety levels.